Ethical and methodological challenges slowing progress in primary care-based suicide prevention: Illustrations from a randomized controlled trial and guidance for future research. (October 2022) - Jerant, Anthony; Duberstein, Paul R.; Kravitz, Richard L.; Kleiman, Evan M.; Rizvi, Shireen L.; Cipri, Camille; Liu, David; Scher, Lorin; Freitas, Melissa; Jones-Hill, Malaika; Oravetz, Aaron; Van Orden, Kimberly A.; et al.
Abstract: Introduction: Despite the pressing need for primary care-based suicide prevention initiatives and growing acknowledgement of recruitment difficulties and Institutional Review Board (IRB) challenges in suicide research, we are aware of no illustrative examples describing how IRB decisions in the design of a primary care trial can compound recruitment challenges. Methods: The CDC-funded trial (NCT02986113) of Men and Providers Preventing Suicide aimed to examine the effects of a tailored computer program encourage men with suicidal thoughts (n = 304, ages 35–64) to discuss suicide with a primary care clinician and accept treatment. Before a visit, participants viewed MAPS or a non-tailored control video. Post-visit, both arms were offered telephone collaborative care, as mandated by the institutional review board (IRB). We previously showed that exposure to MAPs led to improvements in communication about suicide in a primary care visit. In this paper, we report data on the study's primary outcome, suicide preparatory behaviors. Results: After screening nearly 4100 men, 48 enrolled. Recruitment challenges, which were exacerabted by an IRB mandate narrowing post-intervention patient management differences between trial arms, limited detection of the effects of MAPS on suicide preparatory behaviors. Conclusions: While primary care settings are key sites for suicide prevention trials, issues such as recruitment difficulties and overly restrictive IRB requirements may limit their utility. Methodological innovation to improve recruitment and ethical guidance to inform IRB decision-making are needed.